2021
DOI: 10.1002/nop2.948
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of burnout, depression, anxiety and stress in the Lithuanian midwifery workforce and correlation with sociodemographic factors

Abstract: Aim To investigate the prevalence of burnout, depression, anxiety and stress of Lithuanian midwives. Design A descriptive, cross‐sectional survey design. Methods The Work Health and Emotional Wellbeing of Midwives (WHELM) survey instrument developed within the Australian maternity context was adapted and used in this research. The survey collects country‐specific demographic data and incorporates several validated measures including the Copenhagen Burnout Inventory (CBI), Depression, Anxiety and Stress Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(47 reference statements)
2
8
1
Order By: Relevance
“…This study determined a positive relationship between depression, anxiety, stress levels, and burnout levels exist. Similar results are reported in various studies (25,(51)(52)(53). Comprehensive studies are needed to explain the relationship between depression, anxiety, and stress levels of employees and burnout levels in more detail and to determine other factors that may be related.…”
Section: Discussionsupporting
confidence: 84%
“…This study determined a positive relationship between depression, anxiety, stress levels, and burnout levels exist. Similar results are reported in various studies (25,(51)(52)(53). Comprehensive studies are needed to explain the relationship between depression, anxiety, and stress levels of employees and burnout levels in more detail and to determine other factors that may be related.…”
Section: Discussionsupporting
confidence: 84%
“…CBI scores of 100 have previously been interpreted as severe burnout but did not occur in our study. While some previous studies categorized CBI scores <50 as no burnout, we interpret scores of ≥25 and <50 as low burnout and scores <25 as lowest burnout 3,6,9,12,16,29 .…”
Section: Copenhagen Burnout Inventorymentioning
confidence: 82%
“…While we conducted, to our knowledge, the first assessment of burnout dimension levels among midwives in Germany, previous studies have utilized the CBI to assess the levels of burnout among midwives in Australia 3 , 16 - 19 , 33 , 34 , New Zealand 20 , Norway 13 , Sweden 21 , Denmark 15 , 22 , Jordan 35 , the United Kingdom 6 , Ireland 36 , Lithuania 29 , and Canada 12 . These studies found levels of personal burnout and work-related burnout that were comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Job burnout of medical care professionals may not only have a negative impact on personal health, but also affect job satisfaction, resulting in low work efficiency and even medical accidents (Iacobucci, 2021). Previous studies have found that midwives in Australia and United Kingdom experienced a higher incidence of job burnout (Hunter et al, 2019; Vaičienė et al, 2021). In China, most of the studies on job burnout focused on doctors and nurses (Li et al, 2021; Ren et al, 2021; Song et al, 2021).…”
Section: Introductionmentioning
confidence: 96%